New annealing method to improve KD2PO4 crystal quality: learning from high temperature phase transition. Issue 25 (7th July 2015) - Zhang, Lisong; Xu, Mingxia; Liu, Baoan; Zhu, Lili; Wang, Bo; Zhou, Hailiang; Liu, Fafu; Sun, Xun
<x xml:space="preserve">Abstract</x> A new annealing method was developed according to HTPT study, which improved the quality of DKDP crystals effectively.